If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + a = 0 Reorder the terms: a + 5x = 0 Solving a + 5x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5x' to each side of the equation. a + 5x + -5x = 0 + -5x Combine like terms: 5x + -5x = 0 a + 0 = 0 + -5x a = 0 + -5x Remove the zero: a = -5x Simplifying a = -5x
| X(2x)=400 | | 2(x-2)=14+4x | | 4(2x+7)=-50+62 | | 5r-8=10 | | (2-u)(3u-7)=0 | | 6x=6x-22 | | 3x+x=1200000 | | x^2+10x-175=0 | | 3y-27=-16y | | X+23=3x+27 | | V^2+8v-20= | | 9k^2=-9k+28 | | (2x+6)+80=270 | | 7x^3+41x^2-56x=0 | | 2=12t-16t^2 | | 2(2z-8)-28= | | -(2x+7)= | | 3x-13=1x-7 | | 250c+75=1605 | | 7y-56=-16y | | ln(3x-10)=7 | | 3(m+7)-7= | | 7(1+5y)+8= | | 6=2y+5 | | (10-x)(x-1)=4z | | 11=3k-3 | | 1500+10w=1000+30w | | 4x^2+4x=72 | | 9(x+3m+6)= | | (3+5)+2= | | 6x+16=32 | | -4x-3x-41=36 |